2011
DOI: 10.1007/s00198-011-1788-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed collagen improves bone status and prevents bone loss in ovariectomized C3H/HeN mice

Abstract: This study confirms that dietary collagen reduces bone loss in OVX mice by increasing the diameter of the cortical areas of femurs and can have a preventive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 36 publications
(46 reference statements)
5
34
0
1
Order By: Relevance
“…4,[7][8][9][10][11] The effect of CHs on osteoblasts is likely due to its anabolic action, including proliferation and promotion of osteoblastic differentiation. 4,10 The signaling mechanisms of CHs action remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[7][8][9][10][11] The effect of CHs on osteoblasts is likely due to its anabolic action, including proliferation and promotion of osteoblastic differentiation. 4,10 The signaling mechanisms of CHs action remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Oral administration of CHs in ovariectomized rats or mice was also demonstrated to reduce bone loss, 9 and increase bone strength 10 and diameter of the cortical areas of femurs. 11 In a previous study, we have demonstrated that CHs (<3 kDa) have growth promoting effects on the longitudinal bone in adolescent rats. 4 However, an in-depth study on the action mechanisms of CHs has not been carried out.…”
Section: Introductionmentioning
confidence: 98%
“…A second study by the same group showed that the HC administration for 3 or 6 months significantly prevented bone loss in OVX mice (Guillerminet et al, 2012). The authors further demonstrated that HC ingestion for 3 months is as efficient as raloxifene to protect 3-month-old OVX mice from bone loss.…”
Section: Evidence From Animal Modelsmentioning
confidence: 91%
“…The observed effects on body composition and blood plasma parameters could be partly related to a difference in AA profile, as casein is richer than soy primarily in methionine, and also in proline, serine, threonine, glutamine, valine, tyrosine, isoleucine, and leucine (8789). Previous studies suggested that reduction of particular AAs in the diet can extend lifespan in mice and rats.…”
Section: Protein Quantity/qualitymentioning
confidence: 99%
“…Incidentally, those models have been setup to study not only consequences of estrogen deficiency on obesity but also on various diseases including cancer, osteoporosis, cardiovascular diseases, and inflammation. Using the OVX C3H/Hen mice model to induce bone loss, studies (88, 89) have shown that even when the surgery was performed at 3 or 6 months, the procedure induced an increase in body weight related to an increase in the visceral and subcutaneous fat mass. However, when the OVX procedure was performed at 6 months, reduction of uterus weight was not observed compared to Sham mice.…”
Section: Impact Of Estrogen Deficiency On Body Weight and Physiologicmentioning
confidence: 99%